'Only to reconcile with it'. The coping experience amongst middle‐aged and older cancer survivors: A qualitative study - Yi He; Wei Zhao; An Duan; Hong Xiao; Xuemei Zhou; Qiqi Zhuo (Wiley, 2024)
Abstract Background Cancer threat is relevant to age, and the threat of a foreshortened life coupled with a lengthy treatment process negatively affects middle‐aged and older adults. Understanding the coping throughout the cancer experience in middle‐aged and older cancer survivors will help develop supportive care to promote their physiological and psychological coping effects. Objectives To explore the cancer coping experiences of middle‐aged adults aged 40-59 and older adults over 60. Design A descriptive phenomenological study was employed. Methods Face‐to‐face, in‐depth, semistructured interviews were conducted with 22 oncology patients in a tertiary university hospital aged 40 or above from August to October 2023. The interview data were analyzed using thematic analysis procedures. Results Five themes and 13 subthemes were formed through analysis: acceptance of cancer (considering cancer as chronic, believing in fate and attributing cancer to karma); having different information needs (desired to be truthfully informed, information‐seeking behaviour, information avoidance behaviour); getting families involved (developing dependent behaviours, feeling emotional support, family members suffering worse); striving to maintain positive psychological state (positive thinking, seeking peer support) and negative experience (undesirable, low self‐esteem). Conclusion Our study reveals that cancer survivors' attitudes towards having cancer have changed from a death sentence to a more positive perception of a chronic disease. Supportive programmes for developing coping strategies should consider the cultural traditions and religious beliefs, different information needs, involvement of family and promoting a positive psychological state while avoiding negative factors. Patient or Public Contribution Participants with experience of coping with cancer were involved in the semistructured interview.